Drink and Think: Impact of Alcohol on Cognitive Functions and Dementia – Evidence of Dose-Related Effects - Gutwinski, Stefan; Schreiter, Stefanie; Priller, Josef; Henssler, Jonathan; Wiers, Corinde E.; Heinz, Andreas (Pharmacopsychiatry, 2018)
Regular alcohol consumption affects cognitive performance and the development of dementia. So far, findings are contradicting, which might be explained in part by dose-related effects. For this narrative review, we undertook a literature search for surveys investigating the impact of alcohol consumption on cognitive performance and the development of dementia. The majority of studies observed a U-shaped relationship between regular alcohol consumption and cognitive function: frequent heavy consumption of alcohol alters brain functions and decreases cognitive performance; regular light and moderate consumption may have protective impact. In many studies, total abstainers show an inferior cognitive performance than people with moderate or light consumption. Nevertheless, policy implications are difficult to draw for at least 2 reasons: (1) the possible risks associated with alcohol consumption and (2) the potential confounders in the group of non-consumers and heavy consumers.
Keywords: alcohol; dose; dementia; cognitive performance